Kajian Ta’lim Muta’allim Tentang Nilai-Nilai Pendidikan Akhlak - Syahid, Mar (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2019)
Muta'alim Ta'lim Study of Values of Moral Education. The background in writing this scientific paper is education is something that must be taken by everyone. Existing education should be able to produce children who excel in the intellectual, emotional and spiritual. All education is important, but the author will explain about moral education, because according to the authors of moral education is the answer in solving the moral crisis in this nation. The problem of this writing is what are the values of moral education in the book Ta'limul Muta’allim in education today. The purpose of this study is to describe and know the values of moral education contained in the book Ta'limul Muta’allim. This research is a research library research. With the object of literature study material, primary and secondary sources from the book ta’limulmuta’allim. In the process of analyzing the author using Content Analysis in drawing conclusions using the deductive method, the results of this study indicate; moral education values in the book Ta'limul Muta’allim are divided into several points, namely morals to God, morals to humans and morals to science. It is very suitable if implemented in the world of formal education in Indonesia because it will form a virtuous national character.